An Analysis of Language Learning Strategies Used by EFL Student Teachers at English Language Education Program Universitas Negeri Padang - Trinanda Mahdiyah Lestari; Sitti Fatimah (Universitas Negeri Padang, 2020)
The current study was carried out with the intention of investigating the EFL student teachers’ Language Learning Strategies (LLS) in learning English. This study also aims for exploring the level of using LLS and identifying the most and least preferred strategy employed by EFL student teachers at English Language Education Program, Universitas Negeri Padang. This research used a descriptive quantitative method. The total sampling technique is used to all participants of EFL student teachers grouped at International classes enrolled in 2017-2019. The data were gathered through the Strategy Inventory for Language Learning (SILL) questionnaire version 7.0 developed by Oxford and administered to all 82 international EFL student teachers. SILL consists of 50 statements which have six categories as well as Memory, Cognitive, Compensation, Metacognitive, Affective, and Social. The data were analyzed through M.Excel and SPSS version 25. The result indicated all international EFL student teachers employed all strategies categorized as the High level with the average Mean score (M=3.80). The most frequently used is Metacognitive strategy (M=4.01) and the least frequently used is Affective strategy (M=3.53). It can be concluded that language learning strategies are important in raising the learners’ learning awareness and improve educators’ teaching preference.